2020
DOI: 10.21203/rs.3.rs-64515/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interviewing children: the impact of the COVID-19 quarantine on children’s changes in routine and psychological distress. 

Abstract: Background: The COVID-19 outbreak has resulted in governments implementing disease containment measures such as school closures, social distancing, and home quarantine.To date, only a few studies have drawn attention to the psychological impact of lockdown on Italian children’s mental health. The present study aimed to investigate the psychological distress (anxiety and mood symptoms) and changes in routine among Italian primary and middle school students during the COVID-19 quarantine.Methods: This qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Of the 72 studies, 24(33%) were cohort studies, 23 of which used an external historical/retrospective comparison group 22-44 and 1 a parallel comparison group; 45 33 (46%) were cross-sectional studies; 46-78 14(19%) were uncontrolled pre-post studies, 11 of which included one measurement pre- and post-exposure 79-90 and 3 included repeated measures; 91-93 and 1(1%) was a modelling study. 94…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 72 studies, 24(33%) were cohort studies, 23 of which used an external historical/retrospective comparison group 22-44 and 1 a parallel comparison group; 45 33 (46%) were cross-sectional studies; 46-78 14(19%) were uncontrolled pre-post studies, 11 of which included one measurement pre- and post-exposure 79-90 and 3 included repeated measures; 91-93 and 1(1%) was a modelling study. 94…”
Section: Resultsmentioning
confidence: 99%
“…Forty five studies (63%) were high-quality (eTables 3 to 7); 23 cohort studies, 22-44 17 cross-sectional, 46,48,52,54,56,59,61,62,64,65,67,71-74,76,78 4 pre-post, 82,83,91-93 and 1 modelling study. 94 Eighteen (25%) were medium-quality; 13 cross sectional, 49-51,53,55,57,58,60,66,68,70,75,77 and 5 pre-post studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As one key example of a broad pandemic stressor, families around the world report being affected by quarantine and mandatory social distancing (Brooks et al, 2020). These quarantine practices result in challenges to work-family balance through less support for parents from employers and spouses Craig & Churchill, 2020), unemployment (Brown et al, 2020), online schooling demands (Segre et al, 2020), and increased caregiver burden (Russell et al, 2020;Patrick et al, 2020). Although quarantine may entail spending more time at home with family, Ammar et al (2020) found that family members in Asia, Africa, and Europe reported feeling more socially isolated as a result of fewer opportunities to visit with family outside of the home as well as friends and neighbors during quarantine.…”
Section: Pandemic Life Events As Family Stressorsmentioning
confidence: 99%
“…Although some of these changes result in stressors that challenge family functioning (Chung, Chan et al, 2020;Fontanesi et al, 2020) others may offer opportunities to preserve or even bolster family functioning in the face of the pandemic (Orgilés et al, 2020). Emerging research from around the world documents the impact of the COVID-19 and previous epidemics/pandemics on families in terms of economic and resource loss, work-related stress, isolation and separation, illness and exposure concerns, caregiving burdens, and schooling needs for children (Ammar et al, 2020;Brooks et al, 2020;Brown et al,, 2020;Craig & Churchill, 2020;Del Boca et al, 2020;Garcia de Avila et al, 2020;Hawryluck et al, 2004;Orgilés et al, 2020;Saurabh & Ranjan, 2020;Segre et al, 2020). Evidence that these stressors impact the mental and physical health of both parents and children is growing (Brown et al, 2020;DelBoca;Origlés et al, 2020;Patrick et al, 2020;Saurabh;Segre et al, 2020;Xie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%